Using Internet Data to Analyse the Labour Market: A Methodological Enquiry - Lucia Mýtna Kureková; Miroslav Beblavy; Anna-Elisabeth Thum (Institute for the Study of Labor (IZA), 2014)
With the growth of the Internet, online job portals have become an important medium for job matching. This paper focuses on methodological issues arising from the usage of online job vacancy data and voluntary web-based surveys to analyse the labour market. In addition to providing a comprehensive review of the literature based on online data, we highlight the advantages and possible disadvantages of using online data and suggest strategies for overcoming selected methodological issues. We underline the difficulties in adjusting for representativeness of online job vacancies, but nevertheless argue that this rich source of data should be exploited.
Keywords: E4; J2; 330; internet; job; labour market; matching; methodology; occupation; online; representativeness; vacancy